Benefits of Tiwai Onion (Eleutherine americana) Extract as Phytopharmaceutical Plant to Inhibit the Growth of Vibrio harveyi Through in-Vitro and in-Vivo - Azis Azis; Jimmy Cahyadi (Jurnal Ilmiah Perikanan dan Kelautan, 2020)
HighlightsEleutherine americana was a plant that was known to contain antibacterial alkaloids, steroids, phenolics, and flavonoidsEleutherine  americana extract was able to inhibit the development of V. harveyi both through in vitro and in vivo tests on tiger shrimp (Penaeus monodon).The use of vibriosis antibiotics in tiger shrimp was often not controlled so the results obtained were not effective AbstractThe use of vibriosis antibiotics in tiger shrimp was often not controlled, so the results obtained were not effective. The addition of antibiotics would cause resistance to V. harveyi. Eleutherine americana is a plant that is known to contain antibacterial alkaloids, steroids, phenols, and flavonoids. This study aimed to determine the effectiveness of inhibitory effects of E. americana extract against V. harveyi through in-vitro and in-vivo tests on tiger shrimp larvae. In-vitro testing consisted of 7 treatments and 3 replications, namely treatments A (0.1%), B (0.2%), C (0.3%), D (0.4%), E (0, 5%), F ethanol 70% (K-), and G chloramphenicol 0.01% (K +) treatment. The largest inhibition zone diameter of E. americana extract was shown in treatment C (0.3%), with an average value of the inhibition zone produced of 7.5 mm. Challenge test with V. harveyi concentration of 107 CFU / ml in the in-vivo test consisted of 5 treatments and four replications namely; A treatment without E. americana extract, B extract 6 ppm, C extract 12 ppm, D extract 18 ppm, and treatment E without extract and V. harveyi. The results of the challenge test with V. harveyi bacteria were significantly different in control (chloramphenicol 0.01%), where the highest survival rate was in the treatment of 12 ppm extract (43.34%). E. americana extract could inhibit the development of V. harveyi bacteria both through in-vitro and in-vivo tests on tiger shrimp (Penaeus monodon).